The Role of Job Satisfaction Mediation in Competence and Non-Financial Compensation on Employee's Work Performance of PT. PNM Probolinggo Branch - Jacklyn Edmonda Georgiene Deseriere; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
Role of job satisfaction mediation on competency and nonfinance compensation on work performance of employees of PT. PNM Probolinggo Branch. 100 employees of PNM Probolinggo Branch Area 1 Mekaar program. The sampling technique used the census method, the total were 100 employees. data analysis method using SEM and Smart PLS Software. It showed that competence affecting job satisfaction in the PNM Probolinggo branch area 1 of the Mekaar program. Nonfinance compensation affecting job satisfaction in the PNM Probolinggo branch area 1 of the Mekaar program. Competence affecting work performance in the PNM Probolinggo branch area 1 of the Mekaar program. Nonfinance compensation not affecting work performance in the PNM Probolinggo 1 branch area of the Mekaar program. Job satisfaction affecting work performance in the PNM Probolinggo branch area 1 of the Mekaar program